1998
DOI: 10.1046/j.1469-8137.1998.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble and membrane symbiosis‐related polypeptides associated with the development of arbuscular mycorrhizas in tomato (Lycopersicon esculentum)

Abstract: To analyse the effect of arbuscular mycorrhizal (AM) colonization on tomato gene expression, two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) patterns of crude extracts, soluble and membrane proteins of tomato roots, either mycorrhizal and the AM fungus Glomus mosseae (Nicol. & Gerd.) Gerd. & Trappe or nonmycorrhizal, have been compared. In the three fractions analysed, AM colonization induced up-regulation with down-regulation of the synthesis of polypeptides already present in tomato roots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
(24 reference statements)
2
12
0
3
Order By: Relevance
“…Regarding the proteomic level, there are a number of reports documenting differential protein patterns in mycorrhizal and non-mycorrhizal roots (Pacovsky 1989;Schellenbaum et al 1992;Arines et al 1993;GarciaGarrido et al 1993;Dumas-Gaudot et al 1994;Simoneau et al 1994;Samra et al 1997;Benabdellah et al 1998;Dassi et al 1999;Fester et al 2002;Repetto et al 2003). Using specific antibodies, Wyss et al (1990) identified some of the induced proteins as nodulins.…”
Section: Model Plants In Am Researchmentioning
confidence: 94%
“…Regarding the proteomic level, there are a number of reports documenting differential protein patterns in mycorrhizal and non-mycorrhizal roots (Pacovsky 1989;Schellenbaum et al 1992;Arines et al 1993;GarciaGarrido et al 1993;Dumas-Gaudot et al 1994;Simoneau et al 1994;Samra et al 1997;Benabdellah et al 1998;Dassi et al 1999;Fester et al 2002;Repetto et al 2003). Using specific antibodies, Wyss et al (1990) identified some of the induced proteins as nodulins.…”
Section: Model Plants In Am Researchmentioning
confidence: 94%
“…In view of the AM symbiosis-highly specific membrane-related features, sub-cellular proteomics targeting the root microsomal fraction has been suggested to be more relevant to address core functional proteins in mycorrhiza. Alterations in the root membrane polypeptide patterns during the development of arbuscular mycorrhiza were first reported in tomato (Benabdellah et al, 1998(Benabdellah et al, , 2000. However, only one protein, corresponding to a down-regulated vacuolar plant H + -ATPase subunit, could be identified following N-terminal sequencing (Benabdellah et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…In the first of these studies microsomal proteins of tomato roots colonized by G. mosseae were analyzed and a number of spots were shown be responsive to AM mycorrhization [79].…”
Section: Membrane Proteins and Arbuscular Mycorrhizal Interactionsmentioning
confidence: 99%